ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Sektor Makanan dan Minuman Periode 2020-2022) - Manasikana, Arina; Putra, Yanuar Surya; Riyanti, Budi (Universitas Wahid Hasyim, 2024)
All publicly traded firms are required by OJK laws to file their annual reports on time. Financial reports become more valuable if they are submitted following the designated reporting time, which is why timely submission of financial reports is intended to enable users to examine reports in a timely and pertinent manner. The purpose of this study is to ascertain, partially or concurrently, the impact of return on assets, debt-to-equity ratio, current ratio, business age, and audit opinion on the punctuality of financial report submission in manufacturing enterprises in the food and beverage sector. Secondary data for the 2020â€“2023 period released by the BEI is what was used. This study uses tools from logistic regression analysis and is explanatory. The study's findings indicate that the variables return on assets, debt to equity ratio, current ratio, age of the company, and audit opinion have no significant impact on how quickly a company submits its financial reports. The factors ofÂ return on assets, debt-to-equity ratio, current ratio, firm age, and audit opinion all significantly impact how quickly food and beverage companies produce their financial reports.Keywords: Financial reports, return on assets, debt to equity ratio, current ratio, audit opinion